Comportamento verbal novo e comportamento criativo: uma análise do "Verbal Behavior". - Bandini, Carmen Silvia Motta (Universidade Federal de São Carlos, 2004)
One of the factors indicating the complexity of verbal behavior, defined by Skinner as behavior mediated by the other s action, is the possibility of variation and productivity possibility shown by this behavioral form. The present study analyzed the Skinnerian explanation on the arising of new verbal behavior presented in the book Verbal Behavior. This study systematizes the different kinds of behavioral processes and procedures involved, which, in most cases, do not appear in an organized way in the book. According to Skinner, we understand new verbal behavior as 1) arising of new responses in the individual s repertoire when these topographies already exist in other individuals repertoires, as well as already acquired speaker responses that now are emitted under new controls; 2) new responses produced in a community, thus new to the individual and to the verbal community as a whole. An analysis of a few literary works illustrated the analysis of Skinner s work presented in this study.
Keywords: Behaviorismo (Psicologia); Skinner, Burruhus Frederic, 1904; Behaviorismo radical; Comportamento verbal novo; Comportamento verbal criativo; Radical Behaviorism; New verbal behavior; Creative verbal behavior; CIENCIAS HUMANAS::FILOSOFIA